«Խառնվածք» հասկացության միջնադարյան ընկալումները - Մոսիկյան, Կարինե
In antiquity and the Middle Ages, conceptions of temperament, and their use in theoretical and practical science, differed radically from modern approaches. Changes in the humors (one’s various bodily fluids), were thought to cause changes in the whole body. Thus, their study was deemed important in terms of diagnosis, treatment, prediction of outcome, and prevention of diseases arising from their imbalance. In the Middle Ages, general approaches to the treatment and care of illness were used as correctives for temperamental disorders. This approach was shared by medieval Armenian doctors. The teaching of Hippocrates and Galen concerning the humors was the basis for the medical ideas of Mkhit‘ar Herats‘i, Amirdovlat‘ Amasiats‘i, Grigoris, Abusayid and others. Following after their Hellenic forebears Armenian doctors developed a complex system of disease diagnosis, etiology, pathogenesis, description of clinical symptoms, treatment and care. В античности и средневековье концепции темперамента и их применение в теоретической и практической науке радикально отличались от современных понятий. Количественные и качественные сдвиги органических жидкостей, вызывающие изменения во всем организме, имели важное значение как с точки зрения диагностики, лечения, прогнозирования исхода, так и профилактики возникающих в нем заболеваний. В средние века для уравновешивания отклонений темперамента использовались общие подходы лечения и ухода. Этот подход разделяли и средневековые армянские врачи. Медицинские идеи Мхитара Гераци, Амирдовлата Амасиаци, Григориса, Абусаида и других основывались на учении Гиппократа и Галена о темпераменте, руководствуясь которым, армянские врачи организовали весь комплекс диагностики заболеваний, этиологии, патогенеза, описания клинических симптомов, лечения и ухода.
Keywords: Բնագիտություն; Հնագիտություն